the ANALYSIS OF THE RELATIONSHIP OF THE ROLE OF ORGANIZATIONAL SUPPORT, WORK ENGAGEMENT ON THE SUCCESS OF THE MH02 DRIVING MONITORING SYSTEM IN COAL MINING - pranugroho, bagus (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This research proposes to examine the role of organizational support ,wprk engagement between and MH02 technology in coal mining Design/methodology/approach: The quantitative research technique is referred to as the research method. The target of this research is PT. Pamapersada Nusantara, and the research sample, which consists of 279 respondents, refers to the structural equational modelling model Findings: The findings demonstrated that the respondents believed that each and every hypothesis had been confirmed. Research limitations/implications: This study only focused on analyzing the relationship between the role of organizational support and work engagement which is linked to the successful implementation of the MH02 driving monitoring system technology in coal mining. Other factors, such as performance expectancy, effort expectancy, social influence, facilitating conditions, are not explored in depth. It is important for future research to investigate these additional factors and their potential impact on job performance at Pamapersada Nusantara. Despite these limitations, this research contributes to the understanding of factors influencing work performance in the mining industry and provides insights for practitioners to develop effective interventions to improve work performance among employees. Practical implications: The managerial implications of this research are that companies can increase job satisfaction and work engagement, improve employee performance, achieve their goals, and gain competitive advantage. To support this, PAMA management facilitates the implementation of MH02 technology at the site BRCB (Berau coal site Binungan). This technology is really needed so that incidents and fatigue symptoms can be reduced and detected earlier, so that with reduced incidents the company's performance will increase.. Originality/value: This report originates from research conducted inside a single mining business Paper type: Research paper Keyword: Organizational support, Work engagement, Driving monitoring system, User satisfaction, Net benefit